The Importance of Stakeholders' Engagement in the Implementation and Adoption of E-Procurement in Building Construction Projects in the Federal Capital Territory - Umar, Safiya Mohammed; Abioye, Adekunle Moshood; Mukhtar, Musa Mohammed (African Journal of Stability and Development (AJSD), 2025)
Incorporating stakeholders’ engagement is essential for the successful implementation and adoption of e-procurement in building construction projects across the Federal Capital Territory (FCT). As digital technologies revolutionise the construction industry, e-procurement offers numerous benefits, including increased efficiency, transparency, cost savings, and streamlined procurement processes. However, achieving these advantages depends on the active involvement of key stakeholders, such as government agencies, construction firms, suppliers, policymakers, and technology providers. This study aims to explore the impact of stakeholders’ engagement on e-procurement adoption in the Federal Capital Territory (FCT). The study adopts mixed-methods in data collection and analysis. The participants are stakeholders involved in the e-procurement implementation within FCT Administration. The findings from the study revealed high correlation between stakeholders’ engagement and e-procurement adoption. The key obstacles to e-procurement adoption include resistance to change, insufficient technological infrastructure, inadequate digital literacy, and concerns about cybersecurity. Additionally, the study found that the advantages of e-procurement include shorter procurement cycle times, reduced risks of corruption, improved contract administration, and enhanced project efficiency. The study recommends stakeholders’ education, policy alignment, structured communication systems, and leadership support as strategies to address e-procurement implementation challenges. Collaboration is also emphasised to build trust and facilitate the widespread acceptance of digital procurement solutions. The study serves as a guide to top management towards the adoption of e-procurement.